Determination and comparison of time under tension required to perform 8, 10 and 12-RM loads in the bench press exercise - da Silva Jurandir Baptista; Lima Vicente Pinheiro; Paz Gabriel Andrade; de Oliveira Caroline Reis; D'urso Francisco; Moreira Nunes Rodolfo de Alkmim; de Castro Juliana Brandão Pinto; de Souza Vale Rodrigo Gomes (Sciendo, 2016)
Study aim: To determine and compare the time under tension (TUT) required to perform 8, 10 and 12 repetition maximum (RM) loads in the bench press exercise.